2014
DOI: 10.1007/s12010-014-0799-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Interaction Between Bacillus coagulans and Bacillus thuringiensis S-layers and Calcium Ions by XRD, Light Microscopy, and FTIR

Abstract: S-layer is a self-assemble regularly crystalline surface that covers major cell wall component of many bacteria and archaea and exhibits a high metal-binding capacity. We have studied the effect of the calcium ions and type of solid support (glass or mica) on the structure of the S-layers from Bacillus coagulans HN-68 and Bacillus thuringiensis MH14 upon simple methods based on light microscopy and AFM. Furthermore, the Fourier transform infrared spectroscopy (FTIR) study is indicated that the calcium-S-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The role of slpA in bacterial adhesion to chicken epithelium has been suggested previously. Here, we showed that slpA promoted ESC growth (Fagan and Fairweather 2014;Babolmorad et al 2014;Sleytr et al 2007). When the slpA gene was deleted, ERK1/2 phosphorylation in exposed ESCs was inhibited, whereas slpA overexpression induced ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The role of slpA in bacterial adhesion to chicken epithelium has been suggested previously. Here, we showed that slpA promoted ESC growth (Fagan and Fairweather 2014;Babolmorad et al 2014;Sleytr et al 2007). When the slpA gene was deleted, ERK1/2 phosphorylation in exposed ESCs was inhibited, whereas slpA overexpression induced ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 91%
“…Most bacterial S-layers are composed of a single protein species, the S-layer protein, which greatly varies in size among different bacterial genera (Perras et al 2015;Fagan and Fairweather 2014;Babolmorad et al 2014). S-layers are cell envelope structures ubiquitously found in gram-positive and gram-negative bacteria as well as in Archaea.…”
Section: Discussionmentioning
confidence: 99%